Cross Sections Calculations of 33S(n,α)30Si reaction by using the inverse reaction for the first exited state - Sameera A. Ebrahiem; Israa A. Abbas; Adil M. Ibraheim; Mohammad A. Ameer (مجلة جامعة الانبار للعلوم الصرفة, 2014)
In this study light elements 30Si , 33S for 30Si(α,n)33S reaction as well as α-particle energy from (5.001) MeV to (6.284) MeV are used according to the available data of reaction cross sections with threshold energy (3.959MeV). The more recent cross sections data of 30Si(α,n)33S reaction is reproduced in fine steps in the specified energy range , as well as cross section (α,n) values were derived from the published data of (n,α) as a function of energy in the same fine energy steps by using the principle of inverse reaction . This calculations involves the first exited state of 30Si , 33S in the reactions 30Si(α,n)33S and 33S(n,α)30Si . These data are listing , plotted and dissection .